ANTIOXIDANT PROPERTIES OF OSTEOGENIC APATITE-POLYMER BIOMATERIALS FUNCTIONALIZED WITH PHYTOCOMPOUNDS - Bozhko, Nataliia; Sukhodub, Liudmila; Kumeda, Mariia; Sichnenko, Pavlo; Sukhodub, Leonid (Eastern Ukrainian Medical Journal, 2024)
Background. Innovative methods of regenerating damaged bone involve the use of new materials with incorporated biologically active molecules, stem cells, carbon and metal nanoparticles. Ceramics based on calcium orthophosphates are an alternative to native bone tissue, and their modification with nanoparticles (NPs) to improve the properties and functionality of composites is a new trend in the science of biomaterials. The known toxic effect of NPs on the human body by provoking oxidative stress through the formation of reactive oxygen species (ROS), an excessive amount of which causes DNA damage and death of surrounding cells requires the search for effective antioxidants for biomaterials. Materials and Methods. The study was conducted to review the literature on the use of biologically active compounds of plant origin, characterized by high antioxidant activity and osteoconductive properties, in biomedical engineering. Results. To accelerate implant osseointegration, it is important to protect bone cells from oxidative stress, which increases inflammation and can lead to implant rejection. The use of antioxidants, namely polyphenolic compounds, can improve the biocompatibility of biomaterials and increase their antioxidant properties. The review provides data on the use of such biologically active phytocompounds as extracts of medicinal plants (Fructus chebulae, Aloe vera, Camelia sinensis, Salvia officinalis), naringin, quercetin, kaempferol, resveratrol, catechins. By functionalizing biomaterials, the appropriate concentration of bioactive compounds in the implantation zone is maintained, and their release is controlled, which contributes to the neutralization of ROS, the proliferation and osteogenic differentiation of cells with osteogenic potential, the activity of osteoclasts is suppressed, and various signaling pathways are regulated. Conclusions. The analysis of literature sources has shown that polyphenolic compounds are promising phytocompounds used in the synthesis of innovative osteogenic biocomposite materials. The combination of polyphenols with various materials improves the biocompatibility, antioxidant properties, osteoconductivity and osteoinductivity of biomaterials. The ability of plant polyphenols to reduce inflammation and promote tissue regeneration, including bone, makes them promising compounds in biomolecular engineering.